Analysis of Initial Reading Ability in Dyslexic Students at Elementary School - Aswasulasikin; Sri Pujiani; Ilmanul Yakin; Mazda Leva Okta Safitri; Nurdin Kamil; Ilham Arya Susanto (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
Inclusive education is a fundamental right for all children, including students with dyslexia who experience specific learning difficulties in reading and writing. However, implementing inclusive education in Indonesia still faces numerous challenges, such as inadequate early identification, limited suitable teaching methods, and a lack of understanding of dyslexia among teachers and the community. This study aims to analyse the initial reading abilities of dyslexic students at Gunung Malang Public Elementary School 1. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The findings indicate that four dyslexic students experienced difficulties recognising letters, reading syllables, and comprehending simple sentences. Key contributing factors included confusion over visually similar letters, weak phonological awareness, and insufficient reading practice at home. These reading difficulties negatively impacted students' academic performance, highlighting the need for more adaptive teaching strategies, such as phonics-based approaches, engaging educational media, and sustained support from teachers and parents. With proper methods and support dyslexic students can enhance their reading skills and attain equitable educational opportunities.